2016
DOI: 10.4103/0019-5413.193472
|View full text |Cite
|
Sign up to set email alerts
|

Neglected isolated scaphoid dislocation

Abstract: The authors present a case of isolated scaphoid dislocation in a 40-year-old male that was undiagnosed for 2 months. The patient was treated by open reduction, Kirschner wire fixation, interosseous ligament repair using a suture anchor and Blatt's dorsal capsulodesis. At 6 years followup, his radiographs of wrist showed a normal carpal alignment with a scapholunate gap of 3 mm and no evidence of avascular necrosis (AVN) of the scaphoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…3 Notwithstanding, Baek et al assert that accurate anatomic reduction, ligament repair, and secure fixation have the most impact on prognosis. 6 This case report would also support early operative intervention.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…3 Notwithstanding, Baek et al assert that accurate anatomic reduction, ligament repair, and secure fixation have the most impact on prognosis. 6 This case report would also support early operative intervention.…”
Section: Discussionmentioning
confidence: 60%
“…►Table 1 provides a comprehensive review of all of the reported cases. [1][2][3][4][5][6][7][8][9] The majority of scaphoid dislocations were seen in men (male:female ¼ 46:3); however, the age range was noted to be between 18 to 79 years. The main mechanism was a motor vehicle accident with a forced dorsiflexion and twisting motion of the wrist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are reports of late diagnosis, and both ligament reconstruction or carpal procedures, such as carpectomy of the proximal row, were performed. 6,7 It is important to remember that symptoms of compression of the median nerve could be present, especially in cases of volar dislocation 8 . Szabo et al 9 believe that the complexity of ligament injuries, assessed by radiography, can predict the need for open surgery.…”
Section: Discussionmentioning
confidence: 99%